2013
DOI: 10.5511/plantbiotechnology.13.0816a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the potential for somatic embryogenesis in sugar beet (Beta vulgaris L.) breeding lines and improvement of regeneration efficiency

Abstract: A wide range of genotypes suitable for a plant regeneration system is needed when utilizing genetic transformation techniques to develop new crop cultivars. We examined the regeneration efficiencies for somatic embryogenesis in 61 genetically diverse sugar beet (Beta vulgaris L.) breeding lines developed in Japan using a previously reported procedure. Frequencies of embryogenic callus formation from seedling leaf and petiole explants ranged from 0 to 89% and those of somatic embryo formation from the calli ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…These data suggest that further optimization of the culture media may be necessary for Arundo , as for other bioenergy crops researchers have placed extensive effort in this direction . Also, the ability of plant species to be manipulated in vitro is strongly genotype‐dependent , therefore more effort is needed to screen different accessions and identify genotypes more amenable to in vitro cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that further optimization of the culture media may be necessary for Arundo , as for other bioenergy crops researchers have placed extensive effort in this direction . Also, the ability of plant species to be manipulated in vitro is strongly genotype‐dependent , therefore more effort is needed to screen different accessions and identify genotypes more amenable to in vitro cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several reports have shown that sugar beet breeding lines and cultivars generally exhibit diverse in vitro responses to plant regeneration from friable callus, which illustrates strong genotype dependency of the regeneration in that crop ( Dovzhenko and Koop, 2003 ; Ivic-Haymes and Smigocki, 2005 ; Tomita et al., 2013 ). Importantly, in our analysis AtGRF5 overexpression dramatically improved the recovery of transgenic events in several sugar beet inbred lines, including a genotype that was not amenable for transformation up to date ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many published studies report on the effects of various hormonal treatments on the regeneration, proliferation and propagation of different genotypes of sugar beet via diverse tissues (Mezei et al 2006, Mishutkina and Gaponenko 2006, Gürel et al 2011, Tomaszewska-Sowa 2012, Klimek-Chodacka and Baranski 2013, Tomita et al 2013. However, in spite of the evidence for hyperhydricity provided by them (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…6-benzylaminopurine (BAP) is one of the growth regulators from among the CKs, which has been widely used in sugar beet ovule culture for gynogenesis (reviewed in Aflaki et al 2017). However, the proliferated or regenerated plantlets can be hyperhydric (Tomita et al 2013, Pazuki et al 2017a. A hyperhydric sugar beet subculture on a medium with a new composition or under new conditions takes time and effort to produce a normal plant, which is a costly practice (Tomaszewska-Sowa 2012).…”
Section: Introductionmentioning
confidence: 99%